Aerosol contamination in a rural university dental clinic in south India. - Acharya, Shashidhar; Priya, Harsh; Purohit, Bharathi; Bhat, Meghashyam (International Journal of Infection Control, 2009)
Aerosol and splatter are a concern in dentistry because of possible transmission of infectious agents and their potential effects on the health of patients and dental personnel. The objectives of the study were to assess and compare amount of aerosol contamination produced by ultrasonic scaler and high speed air turbine hand piece in immediate vicinity of patient’s mouth during dental procedures and to determine level and type of microbial contamination present on white coats of dental personnel in a rural dental setting. The Study was conducted in two parts, with assessment and comparison of amount of aerosol contamination produced by ultrasonic scaler and high speed air turbine hand piece in first part and examination of fifty one white coat’s of dental personnel for contamination in second part. The results showed higher colony count during oral prophylaxis which was significantly more than during cavity preparation; and the count was highest from patient’s chest area. Also, gram positive organisms were most dominant organisms seen on white coats and resistant strains were found during antibiotic sensitivity of the identified bacterial colonies in both studies. It was concluded from the study that dental procedures like scaling and cavity preparation caused considerable aerosol contamination in the immediate vicinity of the patient’s mouth and of dentists’ barrier clothing. Key Words: Infection control, Aerosol contamination,Dental, White coat, Rural.